TIPS Creation in a Patient with Situs Inversus Totalis - Chovanec, Vendel n; Krajina, Anton n; Loj k, Mirek; Hulek, Petr; Van sek, Tom s (Cardiovascular and interventional radiology, 2002)
We describe the successful creation of a transjugular intrahepatic portosystemic shunt (TIPS) in a patient with complete situs inversus using a simple modification of the standard TIPS technique.We describe the successful creation of a transjugular intrahepatic portosystemic shunt (TIPS) in a patient with complete situs inversus using a simple modification of the standard TIPS technique.